Effects of Cd and Zn on physiological and anatomical properties of hydroponically grown Brassica napus plants - Benáková, Martina; Ahmadi, Hassan; Dučaiová, Zuzana; Tylová, Edita; Clemens, Stephan; Tůma, Jiří (Environmental science and pollution research international, 2017)
Clarifying the connection between metal exposure and anatomical changes represents an important challenge for a better understanding of plant phytoextraction potential. A hydroponic screening experiment was carried out to evaluate the effects of combined interactions of Cd and Zn on mineral uptake (Mg, K, Ca, Na) and on the physiological and anatomical characteristics of Brassica napus L cv. Cadeli, Viking, and Navajo. Plants were exposed to 5 μM Cd (CdCl2), 10 μM Zn (ZnSO4), or both Cd + Zn, for 14 days. Cadmium exposure led to a significant reduction in root growth, shoot biomass, and chlorophyll content. After Cd-only and Cd + Zn treatment, primary root tips became thicker and pericycle cells were enlarged compared to the control and Zn-only treatment. No differences between metals were observed under UV excitation, where all treatments showed more intensive autofluorescence connected with lignin/suberin accumulation compared to control conditions. The highest concentrations of Cd and Zn were found in the roots of all tested plants, and translocation factors did not exceed the threshold of 1.0. The root mineral composition was not affected by any treatment. In the shoots, the Mg concentration slightly increased after Cd-only and Cd + Zn treatments, whereas Zn-only treatment caused a sharp decrease in Ca content. Slight increases in K were seen after the addition of Zn. Significantly higher concentrations of Na were induced by Cd- or Zn-only treatment.
Keywords: Mineral uptake; kořeny rostlin; Biodegradation, Environmental; biodegradace; Soil Pollutants; Cadmium; zinek; Cadmium uptake; látky znečišťující půdu; Zinc; Root anatomy; hydroponie; Plant Roots; Zinc uptake; Hydroponics; Brassica napus; Phytoextraction; kadmium